Research Progress on the Therapeutic Mechanisms of Stigmasterol for Multiple Diseases - Juan Li; Xinhua Zheng; Jinxu Qi (Molecules)
Stigmasterol is a plant-derived phytosterol that has attracted considerable attention because of its diverse biological activities and potential therapeutic applications. In this review, the chemical properties, biosynthesis, and biological effects of stigmasterol are exhaustively summarized. Furthermore, the anti-inflammatory, antioxidant, anticancer, neuroprotective, and hypolipidemic activities of stigmasterol have been discussed. Findings from various in vitro and in vivo studies have revealed its potential in treating various diseases, including cancer, diabetes, neurological disorders, and inflammatory conditions. The mechanisms underlying these effects are also discussed, particularly emphasizing the regulation of key signaling pathways and molecular targets, to further clarify the therapeutic role of stigmasterol. This review would provide a reference for further exploring the utility of stigmasterol as a therapeutic agent, thereby contributing to the improvement of human health.